miR-210 is a target of hypoxia-inducible factors 1 and 2 in renal cancer, regulates ISCU and correlates with good prognosis. - McCormick, R; Blick, C; Ragoussis, J; Schoedel, J; Mole, D; Young, A; Selby, P; Banks, R; Harris, A (2013)
BACKGROUND: Clear cell renal cancer frequently harbours von Hippel-Lindau (VHL) gene mutations, leading to stabilisation of the hypoxia-inducible factors (HIFs) and expression of their target genes. We investigated HIF-1 and HIF-2 in the regulation of microRNA-210 (miR-210), and its clinical relevance in renal tumours. METHODS: RCC4 and 786-O renal cancer cell lines transfected with either an empty vector or functional VHL and incubated in normoxia or hypoxia were examined for miR-210 expression. Hypoxia-inducible factor siRNAs were used to examine their regulation of miR-210. Seventy-one clear cell renal tumours were sequenced for VHL mutations. Expression of miR-210, VHL, CA9, ISCU and Ki-67 were determined by immunohistochemistry and qRT-PCR. RESULTS: In addition to HIF-1 regulating miR-210 in renal cancer, HIF-2 can regulate this microRNA in the absence of HIF-1. MicroRNA-210 is upregulated in renal cancer compared with normal renal cortex tissue. MicroRNA-210 correlates negatively with its gene target ISCU at the protein and mRNA level. MicroRNA-210 correlated with positive outcome variables and negatively with Ki-67. CONCLUSION: We provide further evidence of miR-210 activity in vivo, and show that high miR-210 expression is associated with better clinico-pathological prognostic factors.